(untitled) (Revista de Psicología, 2019)
The present study aimed to analyze whether the time children take to recode a word affects the ability to store the orthographic form of that word. For this, 40 third graders phonologically recoded orthographically complex pseudowords. Precision and reading time were measured. Three days after reading sessions, a dictation and lexical decision tests were assessed. Results showed that orthography learning measures correlated with reading time but not accuracy recoding. These data seem to suggest that, in transparent orthographies like Spanish, reading time has more impact than recoding accuracy in the formation of orthographic representations.